INCIDENCE OF FETOMATERNAL OUTCOMES IN CASES WITH MORBIDLY ADHERENT PLACENTA - KHALID, U; GUL , PI; MAZCURI , M; QURESHI , MAI; RIAZ , S; SALEEM , M (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in tertiary hospitals’ Department of Obstetrics and Gynaecology from January 2022 to June 2022 to assess the incidence of feto-maternal outcomes in cases with morbidly adherent placenta. The study was conducted on 155 women fulfilling the inclusion criteria. Demographic and medical data were recorded. The procedure was performed using a lower-segment approach, and complications were managed according to protocol. Results showed that of 155 women, post-partum hemorrhage occurred in 35.5%, massive blood loss in 66.5%, bladder injury in 14.2%, maternal ICU admission in 35.5%, maternal mortality in 9%, small for gestational age in 21.9% and NICU admission in 26.5%. Results showed that morbidly adherent placenta could cause life-threatening feto-maternal complications; placental disorders must be diagnosed and managed to reduce morbidity and mortality.